A catalyst suitable for an inverse water gas shift reaction driven by an alternating electromagnetic field

CN122999203APending Publication Date: 2026-10-30XIAN XIPU FUTURE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611161884.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本发明提供一种用于交变电磁场驱动RWGS反应的催化剂及其制备方法,旨在从本质上解决能量耦合效率问题

Benefits of technology

实现了从“功能混合”到“结构功能分离”。传统RWGS催化剂通常采用两种设计思路:一是“功能混合”思路,即将具有催化活性的组分与提供热传导或结构支撑的惰性载体(如Al2O3、SiO2、分子筛等)简单复合,但惰性载体会稀释磁性组分,导致电磁感应效率低下;二是“自耗牺牲”思路,即利用高活性、高磁性的单一或多元金属材料(如Fe、Fe-Ni合金)直接作为催化剂,但这类无负载催化剂在高温下易烧结、易积碳,机械强度与长期稳定性差。本发明将结构与功能分离,选用四氧化三铁、碳毡、泡沫金属等兼具优异电磁感应响应与良好机械强度和热稳定性的材料作为专用感应载体,将“能量耦合”与“催化活性”两个核心功能解耦。载体专职高效吸收电磁能并将其转化为热能,而Cu/Mo/Fe等活性中心与K/Na等助剂则专司催化反应。这种设计从根本上解决了传统催化剂“耦合效率”与“催化稳定性/活性”难以兼得的矛盾,实现了能量输入与化学转化的高效协同。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999203A_ABST
    Figure CN122999203A_ABST
Patent Text Reader

Abstract

The application provides a catalyst suitable for an inverse water gas shift reaction driven by an alternating electromagnetic field and a preparation method and application thereof. The catalyst is composed of a carrier, a main active center and an additive, the carrier is selected from one of ferriferrous oxide, carbon felt, foamed iron and foamed copper, the main active center is any two metals of copper, molybdenum and iron, and the additive is potassium or sodium. The catalyst has excellent electromagnetic induction response characteristics and catalytic activity, realizes efficient coupling with an alternating electromagnetic field and rapid heating. The preparation method comprises the following steps of carrier pretreatment, metal salt solution preparation, deposition and precipitation, aging and washing, drying, calcination and reduction activation. The catalyst is specially used for a high-pressure high-space velocity RWGS reaction driven by an alternating electromagnetic field, the CO2 conversion rate is greater than 55%, the CO selectivity is greater than 99.9%, the stability is more than 1000 hours, the molar ratio of product H2 / CO can be finely controlled in the range of 1:1 to 3:1, and the catalyst can be directly used for Fischer-Tropsch synthesis or methanol synthesis to produce sustainable aviation fuel and other high-value chemical products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalysts and their preparation and application technology, specifically to a catalyst suitable for reverse water-gas shift reaction driven by alternating electromagnetic fields, its preparation method and application. Background Technology

[0002] With the continuous increase in global carbon emissions, the resource utilization of CO2 has become a key link in achieving the "dual carbon" goal. Reverse water-gas shift (RWGS) reaction can efficiently convert CO2 into syngas (CO + H2), which can then be coupled with processes such as Fischer-Tropsch synthesis to become an important raw material for the production of green chemicals such as sustainable aviation fuel (SAF), thus attracting much attention. The core of the RWGS reaction lies in the catalyst's adsorption and activation capabilities for CO2 and H2. Currently, related research mainly focuses on metal oxides such as Fe2O3 and Co3O4, which are inexpensive, abundant, and have good activation capabilities for CO2. However, traditional metal oxide catalysts have significant drawbacks: at high temperatures (>600℃), they are prone to active phase sintering and carbon deposition, leading to deactivation; while at low temperatures (<400℃), their activation capability for H2 is weak, resulting in limited CO2 conversion. To improve low-temperature activity, existing technologies typically introduce noble metals (such as Pt and Pd) as promoters, but this significantly increases catalyst costs and weakens its industrial economics. On the other hand, the RWGS reaction is a strongly endothermic process. Traditional external resistance heating methods are not only energy-intensive, but also prone to exacerbating catalyst sintering due to overall heating. In recent years, catalytic technologies driven by renewable energy power have become an important development direction. Among them, alternating electromagnetic field catalytic technology has shown significant advantages in achieving localized, rapid, and in-situ heating of the catalyst. This technology can significantly reduce energy consumption, avoid overall reactor overheating, and is expected to inhibit catalyst sintering.

[0003] However, currently used catalysts, whether supported metal oxides or noble metal catalysts, are not designed for the energy coupling characteristics of alternating electromagnetic fields. They either have weak electromagnetic response capabilities or are expensive. More importantly, in traditional catalysts, the active components are dispersed on the support, which greatly dilutes the volume concentration of the magnetic components, resulting in low induction heating efficiency, slow temperature rise, and high energy consumption in alternating electromagnetic fields.

[0004] Therefore, developing a dedicated catalyst that combines high activity, high selectivity, and excellent stability, and especially one that can be efficiently coupled with alternating electromagnetic fields to achieve rapid heating, has become the key to promoting the industrialization of this technology. Summary of the Invention

[0005] This invention provides a catalyst for RWGS reaction driven by alternating electromagnetic fields and a method for its preparation, aiming to fundamentally solve the problem of energy coupling efficiency.

[0006] To achieve the above objectives, the present invention provides a catalyst comprising a support, a main active center, and an additive. The support is a material with excellent electromagnetic induction response characteristics, selected from one of iron(III) oxide, carbon felt, foamed iron, and foamed copper; the main active center is supported on the surface of the support and is a combination of any two metals selected from Cu, Mo, and Fe; the additive is supported on the surface of the support and is selected from one of K or Na. Based on the mass of the support, the total loading of the main active center is 5%-25% of the support mass, and the molar ratio of the two metals is 1:3 to 3:1; the loading of the additive is 0.5%-3% of the support mass.

[0007] The core innovation of the above technical solution lies in the proposed design concept of "structure-function separation": a material with excellent electromagnetic induction response, good mechanical strength, and thermal stability is selected as a dedicated induction carrier, which is dedicated to efficiently absorbing electromagnetic energy and converting it into thermal energy (energy coupling function); while the Cu / Mo / Fe bimetallic active center and K / Na promoter loaded on it are dedicated to catalytic reaction (catalytic function). This design fundamentally solves the contradiction in traditional catalysts, where the use of inert carriers leads to low electromagnetic response efficiency, or the use of carrierless magnetic materials leads to poor mechanical strength and stability, thus achieving highly efficient synergy between energy input and chemical conversion.

[0008] Furthermore, the present invention also provides a method for preparing the above-mentioned catalyst, characterized by employing a deposition-precipitation method, comprising the following steps: Step S1. Carrier Pretreatment: The selected carriers (Fe3O4, carbon felt, iron foam, and copper foam) are pretreated. For Fe3O4 particles, they are ultrasonically cleaned in deionized water and anhydrous ethanol for 15-30 minutes in sequence to remove surface impurities, and then dried at 60-100℃ for later use. For carbon felt and metal foam, they are ultrasonically cleaned in acetone, dilute hydrochloric acid (0.1-0.5M), and deionized water for 15 minutes each to remove oil and surface oxide layer, and finally vacuum dried at 60-80℃.

[0009] Step S2. Preparation of metal salt solution: According to the preset molar ratio of the main active metal (select any two from Cu, Mo, and Fe, with a molar ratio of 1:3 to 3:1) and the total loading (5%-25% of the carrier mass), weigh the corresponding soluble metal salt (such as nitrate, chloride, or molybdate), dissolve it in deionized water, and prepare a mixed metal salt solution with a concentration of 0.1-1.0M. At the same time, according to the auxiliary agent loading (0.5%-3% of the carrier mass), weigh potassium salt or sodium salt (such as KNO3 or NaNO3), add it to the above solution, and stir evenly.

[0010] Step S3. Deposition and precipitation: Place the pretreated support in a reaction vessel, add the prepared mixed metal salt solution, and stir and disperse evenly under a water bath at 30-80℃. Then, under vigorous stirring, slowly add the precipitant solution (such as 0.1-1.0M Na2CO3, NaOH, or NH3·H2O solution), controlling the dropping rate to gradually increase the pH value of the system to 8.0-10.0, and maintain constant temperature and stirring within this pH range for 1-4 hours, so that the metal ions are uniformly deposited on the surface and in the pores of the support in the form of hydroxides or carbonates.

[0011] Step S4. Aging and Washing: After stopping stirring, allow the suspension to stand at room temperature for 2-6 hours to age, allowing a stable interfacial bond to form between the sediment and the carrier. Then filter to separate the solid product, and wash repeatedly with deionized water until the filtrate is neutral and free of chloride or nitrate ions (tested with AgNO3 or pH paper).

[0012] Drying and calcination: The washed solid product is dried at 80-120℃ for 6-12 hours to remove free moisture. Then the dried sample is placed in a muffle furnace or tube furnace and heated to 350-500℃ at a heating rate of 1-5℃ / min in air or an inert atmosphere, and calcined at a constant temperature for 2-5 hours to decompose the metal hydroxide or carbonate into metal oxide.

[0013] Reduction activation: The calcined sample is transferred to a tubular reduction furnace and heated to 400-650℃ at a heating rate of 2-5℃ / min under a reducing atmosphere (such as 5%-20% H2 / N2 or H2 / Ar mixture). The temperature is maintained for 2-6 hours to reduce the metal oxide to a catalytically active metallic state or a low-valence state, and finally the catalyst is obtained.

[0014] Compared with the prior art, the catalyst and preparation method of the present invention have the following beneficial effects: This invention achieves a shift from "functional hybridization" to "structure-function separation." Traditional RWGS catalysts typically employ two design approaches: one is the "functional hybridization" approach, which involves simply combining the catalytically active component with an inert support (such as Al2O3, SiO2, or molecular sieves) that provides thermal conductivity or structural support. However, the inert support dilutes the magnetic component, leading to low electromagnetic induction efficiency. The other is the "self-sacrifice" approach, which utilizes highly active, highly magnetic single or multi-metal materials (such as Fe or Fe-Ni alloys) directly as catalysts. However, these unsupported catalysts are prone to sintering and carbon deposition at high temperatures, exhibiting poor mechanical strength and long-term stability. This invention separates structure and function, selecting materials such as iron(III) oxide, carbon felt, and metal foam, which possess excellent electromagnetic induction response and good mechanical strength and thermal stability, as dedicated induction supports. This decouples the two core functions of "energy coupling" and "catalytic activity." The support is dedicated to efficiently absorbing electromagnetic energy and converting it into thermal energy, while active centers such as Cu / Mo / Fe and promoters such as K / Na are dedicated to the catalytic reaction. This design fundamentally solves the contradiction between "coupling efficiency" and "catalytic stability / activity" in traditional catalysts, achieving highly efficient synergy between energy input and chemical conversion.

[0015] The energy input method has been adapted from "general external heating" to "dedicated electromagnetic internal heating." Most existing RWGS catalysts are designed for external heating methods such as traditional resistance furnaces, with their core focus on optimizing the intrinsic catalytic performance of the catalyst under steady-state temperature fields. However, the catalyst of this invention is specifically tailored for internal heating processes driven by alternating electromagnetic fields. The selection criteria for the support material (high magnetic loss tangent, high dielectric loss, and excellent conductivity) directly serve the efficient electromagnetic energy-to-thermal energy conversion. For example, Fe3O4 supports generate heat through strong hysteresis loss, while foamed metals generate heat through eddy current effects. This targeted design enables the catalyst to achieve second-level rapid start-up, precise temperature control, and extremely low thermal inertia in alternating electromagnetic fields—something unmatched by any traditional catalyst designed for external heating. This represents a paradigm shift in energy utilization from "heating the entire reaction space" to "precisely heating the catalyst itself."

[0016] In traditional loading processes such as impregnation, the distribution of active metals on the carrier surface is often disordered and uncontrollable, easily leading to agglomeration. The deposition-precipitation method of this invention, through precise control of pH, temperature, and precipitant concentration, promotes the directional and uniform nucleation and growth of active metal precursors on the surface and within the pores of the induction carrier, forming highly dispersed nano-active particles. More importantly, this invention introduces a synergistic system of "dual active metals + additives" onto the electromagnetic induction carrier. By selecting any two of Cu / Mo / Fe as the main active centers, and supplementing with K or Na as electronic additives, the electron density and surface acidity / basicity of the active sites can be precisely controlled at the atomic scale. This specifically promotes the CO generation pathway in the competitive RWGS reaction while simultaneously inhibiting side reactions such as methanation and coking, achieving a significant breakthrough in maintaining high CO selectivity even under harsh conditions (high space velocity, high pressure).

[0017] Traditional catalysts often sacrifice stability in pursuit of high activity, or use large amounts of inert supports to achieve stability, resulting in reduced active site density and energy efficiency. This invention achieves a comprehensive performance leap without sacrificing any single component through a ternary synergistic approach of "high-efficiency inductive support + highly dispersed bimetallic active sites + electronic additive modification." It not only exhibits extremely high energy coupling efficiency and heating rate in alternating electromagnetic fields, but also demonstrates superior CO2 conversion, near 100% CO selectivity, and long-term operational stability exceeding 1000 hours compared to traditional supported and unsupported catalysts under simulated industrial conditions of high space velocity and high pressure. Furthermore, the use of monolithic or foam-like supports results in high mechanical strength, low pressure drop, ease of filling and large-scale production, and excellent compatibility with industrial reactors (especially fixed-bed reactors).

[0018] Furthermore, this invention also provides an application of the above-mentioned catalyst in a reverse water-gas shift (RWGS) reaction driven by an alternating electromagnetic field. The catalyst is loaded into a reactor with a built-in induction coil, and under the action of an alternating electromagnetic field, at 400-620℃, 1.0-4.0 MPa, a feed gas H2 / CO2 volume ratio of 1.2-3.0, and a high space velocity (standard condition 80,000-200,000 h⁻¹). -1 The reaction is carried out under [condition]. The H2 / CO molar ratio in the syngas produced by the reaction can be adjusted to meet the specific requirements of downstream Fischer-Tropsch synthesis or methanol synthesis for the feed gas.

[0019] At 560℃, 1.0MPa, H2 / CO2 volume ratio of 1.5:1, and high air velocity of 150,000 h⁻¹ -1Under harsh conditions, the catalyst of this invention drives the RWGS reaction, achieving a stable CO2 single-pass conversion rate of over 55% and a CO selectivity of up to 99.95%. The H2 / CO ratio in the product gas remains stable at 2, perfectly meeting the feed requirements for downstream Fischer-Tropsch synthesis to prepare SAF, eliminating the complex modulation steps in traditional processes.

[0020] During a long-term test with continuous operation for 1000 hours, the catalyst activity and selectivity remained stable, verifying the high resistance to sintering and carbon deposition of the active phase of the catalyst.

[0021] The catalyst of this invention is specifically designed for coupling with high-pressure green hydrogen. Its high-pressure (1.0-4.0MPa) and high-activity characteristics allow it to be directly connected to the output pressure of green electricity hydrogen production (PEM electrolysis, etc.), reducing system compression energy consumption and providing an integrated, low-energy catalyst solution for CO2 hydrogenation to SAF. Attached Figure Description

[0022] Figure 1 This is a performance diagram of the catalyst of the present invention in an alternating electromagnetic field; Figure 2 This is a comparison of the temperature rise curves of the catalyst of this invention and the comparative inert supported catalyst in an alternating electromagnetic field. Figure 3 This is a scanning electron microscope image of the catalyst supported on carbon felt in this invention. Figure 4 The XRD patterns of the IF catalyst and the Fe3O4 / IF catalyst of this invention are shown. Detailed Implementation

[0023] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. The following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. In the embodiments, the performance of the catalyst is evaluated in a fixed-bed reactor, with an induction coil wound around the reactor periphery and connected to a high-frequency AC power supply to provide an alternating electromagnetic field. The products are quantitatively analyzed using online gas chromatography (equipped with a TCD detector), and the CO2 conversion rate and CO selectivity are calculated according to publicly available formulas.

[0024] Example 1: A catalyst supported on Fe3O4 with Cu-Fe as the main active center and K as an auxiliary agent.

[0025] Catalyst preparation: 50g of Fe3O4 microspheres with a particle size of 50-100μm were ultrasonically dispersed in deionized water for 30 minutes, filtered, and dried at 100℃ for later use. 6.04g of Cu(NO3)3·3H2O (Cu loading of 33.3mol%), 20.20g of Fe(NO3)3·9H2O (Fe loading of 66.7mol%), and 1.01g of KNO3 were weighed and dissolved in 200mL of deionized water with stirring. The total loading of the main active centers was 10% of the support mass. The pretreated Fe3O4 support was added to the above mixed salt solution and stirred in a 70℃ water bath to form a suspension. Under vigorous stirring, 0.5M Na2CO3 solution was slowly added dropwise, controlling the pH of the system at 8.5±0.2. After the addition was complete, the system was aged by stirring at 70℃ for 2 hours. After aging, the sample was filtered, washed with deionized water until the filtrate was neutral, and dried at 110°C for 12 hours. After drying, the sample was calcined in air at 400°C for 3 hours, and then reduced at 500°C for 4 hours in a 10% H2 / Ar atmosphere to obtain the final catalyst, denoted as Fe3O4@Cu-Fe / K.

[0026] Reaction evaluation: at 2.5 MPa and a space velocity of 150,000 h⁻¹ -1 The feed gas ratio is H2 / CO2 = 3:1, and the bed temperature is controlled at 480℃ by an alternating electromagnetic field to carry out the reaction.

[0027] Results: The initial CO2 conversion rate was 57.5%, the CO selectivity was >99.9%, and the product H2 / CO molar ratio was approximately 2.8:1. During 1000 hours of continuous operation testing, the catalyst exhibited good stability, with a conversion rate retention rate greater than 98%.

[0028] Example 2: A catalyst with copper foam as a support, Mo-Fe as the main active center, and Na as an auxiliary agent.

[0029] Catalyst preparation: Copper foam (porosity > 95%) was cleaned and dried. (NH4)6Mo7O was weighed... 242.12 g of 4H₂O (Mo loading accounts for 25 mol% of the total active metal), 8.11 g of FeCl₃·6H₂O (Fe loading accounts for 75 mol%), and 0.59 g of NaCl were dissolved in 150 mL of deionized water. The total loading of the main active centers was 15% of the carrier mass. The pretreated copper foam carrier was completely immersed in the above salt solution, and the pores were filled with solution under vacuum. 1 M NH₃·H₂O was slowly added dropwise at 60 °C until the solution pH=9.0, and the solution was allowed to stand for 3 hours. The carrier was removed, the surface was rinsed with deionized water, and dried at 100 °C for 12 hours. The dried sample was calcined at 450 °C for 2 hours in an Ar atmosphere, and then reduced at 600 °C for 5 hours in a 5% H₂ / Ar atmosphere to obtain the final catalyst, denoted as Cu-foam@Mo-Fe / Na.

[0030] Reaction evaluation: at 3.0 MPa and a space velocity of 80,000 h⁻¹ -1 The feed gas ratio of H2 to CO2 is 1.5:1, and the reaction is carried out at a bed temperature of 600℃ by controlling the temperature with an alternating electromagnetic field.

[0031] Results: The initial CO2 conversion rate was 56.3%, CO selectivity was >99.9%, and the product H2 / CO molar ratio was approximately 1.5:1. After a long-term stability evaluation of 1000 hours, the catalyst activity degradation was negligible, and the conversion rate retention rate was greater than 97%.

[0032] Example 3: A catalyst supported on carbon felt with Cu-Mo as the main active center and K as an auxiliary agent.

[0033] Catalyst preparation: Carbon felt (5 mm thick, porosity > 90%) was cut into cylinders with a diameter of 5 mm. It was first refluxed in concentrated nitric acid at 60 °C for 4 hours to increase the surface oxygen-containing functional groups and roughness. Then, it was washed with deionized water until neutral and finally vacuum dried at 80 °C for later use. 5.52 g of Cu(NO3)2·3H2O (Cu loading accounts for 66.7 mol% of the total active metal) and (NH4)6Mo7O were weighed. 241.77 g of 4H₂O (Mo loading 33.3 mol%) and 0.28 g of KOH were dissolved in 100 mL of deionized water, and the pH was adjusted to weakly alkaline (approximately 8.0) with KOH. The total loading of the main active centers was 12% of the carrier mass. The pretreated carbon felt carrier was immersed in the above metal salt solution and vacuum-treated at room temperature for 30 minutes to ensure that the solution fully wetted the carbon felt pores. Subsequently, the system was heated to 60 °C, and 0.5 M Na₂CO₃ solution was added dropwise under slow stirring until the pH of the system stabilized at 9.0. The reaction was then carried out under constant temperature and stirring for 3 hours to allow the active component precursor to be uniformly deposited on the surface of the carbon felt fiber. After the reaction, the carbon felt was removed, rinsed repeatedly with deionized water, and vacuum-dried at 80 °C for 6 hours. The dried sample was then calcined at 350 °C for 2 hours under N₂ atmosphere by increasing the temperature at 2 °C / min to decompose the precursor. Subsequently, in a 10% H2 / Ar atmosphere, the temperature was raised to 550℃ at the same heating rate and reduced for 3 hours to obtain the final catalyst, denoted as C-felt@Cu-Mo / K.

[0034] Reaction evaluation: at 1.5 MPa and a space velocity of 180,000 h⁻¹ -1 The feed gas ratio of H2 / CO2 is 2:1, and the reaction is carried out at 500℃ by controlling the bed temperature through an alternating electromagnetic field.

[0035] Results: The initial CO2 conversion rate was 55.2%, CO selectivity was >99.9%, and the product H2 / CO molar ratio was approximately 2.0:1. During 1000 hours of continuous operation, the catalyst exhibited excellent mechanical strength and activity stability, with a conversion retention rate greater than 99%.

[0036] Example 4: A catalyst with iron foam as a support, Fe-Mo as the main active center, and Na as an auxiliary agent.

[0037] Catalyst preparation: Foamed iron (porosity > 95%) was cleaned and dried. 10.10 g of Fe(NO3)3·9H2O (Fe loading accounts for 75 mol% of the total active metal) and (NH4)6Mo7O were weighed. 24 • 0.88 g of 4H₂O (Mo loading 25 mol%) and 0.34 g of NaNO₃ were dissolved in 100 mL of deionized water. The total loading of the main active center was 8% of the support mass. Deposition, precipitation, and post-treatment: the steps were the same as in Example 3. The final catalyst was designated as Fe-foam@Fe-Mo / Na.

[0038] Reaction evaluation: at 4.0 MPa and a space velocity of 120,000 h⁻¹ -1 The feed gas ratio of H2 to CO2 is 2.5:1, and the reaction is carried out at a bed temperature of 550℃ by controlling the temperature with an alternating electromagnetic field.

[0039] Results: The initial CO2 conversion rate was 58.7%, CO selectivity was >99.9%, and the product H2 / CO molar ratio was approximately 2.3:1. In the 1000-hour long-term stability test, the catalyst exhibited excellent anti-sintering and anti-coking properties, with a conversion retention rate greater than 98.5%.

[0040] Comparative Example 1: Single Metal Catalyst Supported on Conventional Inert Support Catalyst Design and Preparation: Simulating the most common conventional RWGS catalyst design, a single active metal (Cu) is supported on an inert support (γ-Al₂O₃) without any additives. The support does not possess electromagnetic induction properties and has a single active site. Preparation Method: An equal-volume impregnation method is used. A catalyst with a specific surface area of ​​200 m² / g is prepared. 2 / g of γ-Al₂O₃ spheres (0.5-1.0mm in diameter) are immersed in copper nitrate solution to achieve a theoretical Cu loading of 10wt% (based on the carrier mass). After impregnation, the spheres are dried at 120°C for 12 hours, followed by calcination at 500°C for 4 hours in air. Before use, the spheres are reduced at 400°C for 2 hours in pure H₂ atmosphere. This is denoted as γ-Al₂O₃@Cu.

[0041] Reaction Evaluation: To ensure a fair comparison, the same external heating conditions as in Example 3 of this invention were used (because the catalyst generates almost no heat in an alternating electromagnetic field): in a fixed-bed reactor heated by a conventional resistance furnace, at 500°C, 1.5 MPa, feed gas H2 / CO2 = 2:1, and space velocity 180,000 h⁻¹. -1 The reaction proceeds below.

[0042] Results: The initial CO2 conversion rate was 42.1%, and the CO selectivity was 97.5%. Both the activity and selectivity were significantly lower than those of all embodiments of the present invention. After 200 hours of operation, the CO2 conversion rate decreased to 28.5% (with a retention rate of approximately 67.7%), and obvious carbon deposits were observed on the catalyst surface.

[0043] Comparative Example 2: Single-component catalyst with electromagnetic response (unsupported structure) Catalyst Design and Preparation: This study investigated a material with inherent electromagnetic response capabilities but lacking a supported structure and possessing a single active component. Reduced iron powder (>99.9% Fe) was selected as the catalyst. It exhibits strong ferromagnetism, enabling coupling with electromagnetic fields, but lacks a porous support structure, has an extremely low specific surface area, and is a single Fe active phase. Micron-sized reduced iron powder was compressed into tablets, crushed, and sieved to obtain 40-60 mesh particles. These particles were then pretreated directly in a 10% H₂ / Ar atmosphere at 400°C for 2 hours to clean the surface. This pretreatment is denoted as Bulk Fe.

[0044] Reaction Evaluation: In the same alternating electromagnetic field reactor as Example 1 of this invention (Fe3O4@Cu-Fe / K), the catalyst bed temperature was maintained at 480°C by adjusting the electromagnetic field power. The reaction pressure, feed gas ratio, and space velocity were the same as in Example 1: 2.5 MPa, H2 / CO2 = 3:1, and space velocity 150,000 h⁻¹. -1 .

[0045] Results: The initial CO2 conversion rate was 35.8%, with a CO selectivity of only 85.2% and a high methane (CH4) selectivity of 14%. This indicates that the single Fe phase is more likely to promote the deep hydrogenation of CO2 to methane. After 50 hours of operation, the conversion rate dropped sharply to below 15%. The catalyst exhibited severe agglomeration and sintering after the reaction, forming a large amount of carbon fibers, and its structure was completely destroyed.

[0046] The results are shown in Table 1 below:

[0047] Results analysis: 1. Systematic analysis of catalytic activity and selectivity As shown in Table 1, under high pressure (1.5-4.0 MPa) and high air velocity (80,000-180,000 h⁻¹), -1 Under harsh simulated industrial conditions, the four catalysts provided in this invention (Fe3O4@Cu-Fe / K, Cu-foam@Mo-Fe / Na, C-felt@Cu-Mo / K, Fe-foam@Fe-Mo / Na) all exhibited excellent initial catalytic performance, with CO2 conversion rates greater than 55% and CO selectivity exceeding 99.9%. In contrast, Comparative Example 1 (γ-Al2O3@Cu), using a traditional inert support and a single-metal active center, showed significantly lower initial CO2 conversion rates (42.1%) and CO selectivity (97.5%) under the same external heating conditions. This fully demonstrates that the synergistic design of "bimetallic active center (selected from Cu / Mo / Fe) + alkali metal promoter (K / Na)" adopted in this invention can effectively optimize the electronic structure and reaction sites on the catalyst surface, significantly improving its activation ability for CO2 molecules and selectivity for CO generation pathways. Its technical effect is incomparable to that of a single-metal active center.

[0048] Comparative Example 2 (Bulk Fe), while inherently ferromagnetic and capable of heating in an alternating electromagnetic field, exhibited the lowest initial CO2 conversion rate (35.8%) and severely deteriorated CO selectivity (85.2%), resulting in a large amount of methane as a byproduct. This demonstrates, from the opposite perspective, that electromagnetic response characteristics alone are far from sufficient in RWGS reactions; the chemical composition and structure of the active phase itself have a decisive influence on the reaction pathway. The bimetallic and auxiliary synergistic system of this invention successfully suppressed side reactions such as methanation, achieving near 100% selectivity control over the target product CO.

[0049] 2. Comparative Demonstration of Long-Term Operational Stability One of the core advantages of this invention lies in its superior long-term stability. As shown in Table 1, the catalysts in the four examples maintained a conversion rate of over 97% during continuous operation testing for up to 1000 hours, demonstrating extremely strong resistance to deactivation. Comparative Example 1, however, experienced a significant decline in activity (approximately 68% retention) after only 200 hours of operation due to severe carbon buildup, revealing the common problem of insufficient stability of traditional catalysts in high-temperature reactions. The situation in Comparative Example 2 was even more severe; its carrier-free monolithic iron powder underwent severe sintering and structural collapse within 50 hours, resulting in complete deactivation.

[0050] This stark contrast powerfully demonstrates that the present invention's use of materials such as iron oxide, carbon felt, and foamed metal, which possess excellent electromagnetic induction properties, high thermal conductivity, and high mechanical strength, as dedicated induction carriers not only solves the energy coupling problem but also fundamentally provides robust "anchoring" sites and anti-sintering skeletal support for the active components. Simultaneously, the introduction of highly dispersed active phases prepared by the deposition precipitation method and the additives further inhibits carbon deposition. This triple guarantee mechanism of "stable carrier + highly dispersed active sites + anti-carbon deposition additives" is the fundamental reason for the ultra-long lifespan stability of the catalyst in this invention.

[0051] 3. A comprehensive reflection of energy utilization efficiency and product adjustability The catalyst of this invention is specifically designed for "internal heating" reaction processes driven by alternating electromagnetic fields. The inductive support (such as the hysteresis loss of Fe3O4, or the eddy current / resistance loss of foamed metal / carbon felt) can efficiently and in-situ convert electromagnetic energy into heat energy, achieving rapid heating of the catalyst bed within seconds and precise temperature control, avoiding the huge thermal inertia losses and energy waste of traditional external heating methods. Comparative Example 1, due to the use of an inert support, is completely unable to generate heat effectively in an alternating electromagnetic field, revealing the inadequacy of its energy utilization method.

[0052] Furthermore, as shown in Table 1, by adjusting the H2 / CO2 ratio of the feed gas (1.2:1 to 3:1), the catalyst of this invention can flexibly and precisely control the H2 / CO molar ratio in the product syngas within the range of 1:1 to 3:1 (e.g., 1.5 for product in Example 2 and 2.0 for Example 3). This controllability allows the produced syngas to perfectly adapt to the feed requirements of different downstream process routes such as Fischer-Tropsch synthesis (which typically requires H2 / CO≈2.0) or methanol synthesis, demonstrating extremely high process flexibility and industrial application value.

[0053] In summary, through systematic experimental comparison and data analysis of the catalyst of this invention with representative traditional technical solutions (Comparative Examples 1 and 2), it is fully demonstrated that the catalyst provided by this invention, based on the ternary synergistic design of "inductive support-bimetallic active center-auxiliary agent," successfully solves the major technical challenges of existing RWGS catalysts in terms of multiple dimensions, such as high-efficiency energy coupling, high intrinsic catalytic activity / selectivity, ultra-long-term operational stability, and flexible product tunability, through systematic innovation in material selection (inductive support), active site construction (bimetallic + auxiliary agent), and preparation process (deposition and precipitation method). The comprehensive performance shown in the examples far exceeds that of the comparative examples, achieving unexpected technical effects and demonstrating outstanding creativity. It provides a highly competitive high-performance catalyst solution for CO2 hydrogenation to syngas and subsequent production of green chemical products such as sustainable aviation fuel (SAF).

[0054] The above are merely preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A catalyst suitable for reverse water-gas shift reaction driven by alternating electromagnetic field, characterized in that: The catalyst consists of a support, a main active center, and an auxiliary agent; The carrier is a material with electromagnetic induction response characteristics; The main active center is a metal component loaded on the surface of the carrier, selected from any combination of two metals selected from copper, molybdenum and iron; The additive is an alkali metal element loaded on the surface of a carrier, selected from potassium or sodium.

2. The catalyst according to claim 1, characterized in that, The carrier is selected from one of the following: iron oxide, carbon felt, iron foam, and copper foam.

3. The catalyst according to claim 1, characterized in that, The loading of the main active center is 5%-25% of the carrier mass, and the loading of the adjuvant is 0.5%-3% of the carrier mass.

4. The catalyst according to claim 1, characterized in that, The molar ratio of the two metals in the main active center is 1:3 to 3:

1.

5. A method for preparing a catalyst suitable for an alternating electromagnetic field-driven reverse water-gas shift reaction as described in any one of claims 1-4, characterized in that, Includes the following steps: Step S1: Pre-treat the carrier; Step S2: Prepare a mixed solution containing the main active center metal salt and the auxiliary salt; Step S3: Mix the pretreated carrier with the mixed solution, and add a precipitant to carry out a deposition and precipitation reaction; Step S4. After precipitation, the material is subjected to aging, washing, drying, calcination and reduction activation in sequence to obtain the catalyst.

6. The preparation method according to claim 5, characterized in that, In step S3, the temperature of the deposition and precipitation reaction is 30-80℃, the pH value is 8.0-10.0, and the reaction time is 1-4 hours.

7. The preparation method according to claim 4, characterized in that, In step S4, the calcination is carried out at 350-500℃ for 2-5 hours, and the reduction activation is carried out at 400-650℃ in a reducing atmosphere for 2-6 hours.

8. The application of the catalyst according to any one of claims 1-4 in the reverse water-gas shift reaction driven by an alternating electromagnetic field.

9. The application according to claim 8, characterized in that, The conditions for the reverse water-gas shift reaction include: a reaction temperature of 400-620℃ and a pressure of 1.0-4.0MPa.

10. The application according to claim 8, characterized in that, The H2 / CO2 volume ratio of the feed gas is 1.2-3.0, and the volume hourly space velocity is 80,000-200,000 h⁻¹. -1 The frequency of the alternating electromagnetic field is 1-90kHz.